2012
DOI: 10.1143/apex.5.073101
|View full text |Cite
|
Sign up to set email alerts
|

Undoped and Hole-Doped Superconductors T$'$-La$_{1.8-x}$Eu$_{0.2}$Sr$_{x}$CuO$_{4}$ ($x = 0$ and 0.05) Prepared by Solid-State Reaction

Abstract: We have successfully synthesized La1.8-xEu0.2SrxCuO4 (x = 0 and 0.05) with the Nd2CuO4-type (T'-type) structure by means of the structural transformation at low temperatures from the K2NiF4-type (T-type) structure via the Sr2CuO3-type (S-type) structure. Superconductivity has appeared by postannealing T'-La1.8-xEu0.2SrxCuO4 in vacuum at 700 °C for the removal of excess oxygen. The superconducting transition temperatures are 20 and 13 K for x = 0 and 0.05, respectively. T'-La1.8-xEu0.2SrxCuO4 with x = 0.05 is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 22 publications
4
34
0
Order By: Relevance
“…The SC samples were obtained through the reduction annealing at 700 • C for 24 h in vacuum. Details have been described in the literature [19]. Figure 2 shows the temperature dependence of the magnetic susceptibility of Pr [46].…”
Section: Evolution Of the Electronic State Through The Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SC samples were obtained through the reduction annealing at 700 • C for 24 h in vacuum. Details have been described in the literature [19]. Figure 2 shows the temperature dependence of the magnetic susceptibility of Pr [46].…”
Section: Evolution Of the Electronic State Through The Reductionmentioning
confidence: 99%
“…In 2005, a surprising result was obtained in thin films of the electron-doped cuprates with the Nd 2 CuO 4 -type structure (the so-called T' structure), in which the superconductivity appears without electron doping [17]. Following observations of the undoped (Ce-free) superconductivity in the parent compounds [18,19] and the suggestion of a new phase diagram shown in Figure 1b [20] opened a new era of research in the high-T c superconductivity. Yet to date, the mechanism of the undoped superconductivity is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Values of T c , defined at the onset6 / 14 temperature of the diamagnetic signal, are plotted inFig. 5together with those of hole-doped T'-La 1.8-x Eu 0.2 M x CuO 4 (M = Sr, Ca) reported by Takamatsu et al10,19) It is found that T c increases with increasing y, exhibits the maximum of 23 K at y = 0.025, and decreases. Taking into account T c 's of hole-doped T'-La 1.8-x Eu 0.2 M x CuO 4 (M = Sr, Ca), the carrier-doping dependence of T c is found to be dome-like.Here, we discuss the dome-like dependence of T c on the carrier doping, based on the two possibilities in the electronic state of the undoped (Ce-free) superconductor mentioned in Sec.…”
mentioning
confidence: 91%
“…annealed thin single crystals of Pr 2− x Ce x CuO 4 sandwiched by Pr 2− x Ce x CuO 4 polycrystals of the same compositions and realized superconductivity with Ce concentration as low as 4%. Recently, in thin films2122 and powdered samples2324 of e-HTSCs, superconductivity was found even without Ce doping. Inspired by those studies, Adachi et al 25.…”
mentioning
confidence: 99%